L’archéologue dans la bande dessinée de science-fiction francophone - Rémi Auvertin (ReS Futurae)
Archaeologists are a recurrent and popular motif of science fiction, particularly in literature or cinema : they actively contribute to spatial and temporal exploration or the discovery of lost civilizations. The article offers a synthesis on the treatment of archaeology and its practitioners by French-Belgian science fiction comics, within a wide-ranging corpus (Yoko Tsuno, The Scrameustache, Blake and Mortimer, Infinity 8, Aquablue, Cyrrus, Terres lointaines, etc.). The aim is to analyse in diachrony the identity and profile of these archaeologists, the nature of their scientific and exploratory activities, but also the role given to archaeological practice or its objects in the structure of the narrative and in the creation of an atmosphere of exoticism or mystery. The archaeologist appears mainly in an archetypal form, only challenged by the most recent works. Paradoxically, this synthesis also reveals an absence : if archaeology is an effective tool for introducing a science-fiction or marvelous aspect into everyday life, French-speaking science-fiction makes sparse use of the theme and often prefers an archaeological setting to a direct quotation (Druillet, Mœbius, or Schuiten and Peeters’ Les Cités obscures).